2020
DOI: 10.1111/dth.13313
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the efficacy and safety of secukinumab vs ixekizumab in moderate‐to‐severe psoriasis after 1 year of treatment: Real‐world practice

Abstract: There are no studies which directly compare efficacy in Psoriasis Area and Severity Index (PASI) response of secukinumab and ixekizumab. The main aim of this study was to compare the efficacy and safety of both drugs used to treat moderate‐to‐severe psoriasis patients over 52 weeks. Secondary objectives were to identify which factors related to prior biologic treatment influenced their efficacy and analyze data obtained at 12 weeks. A retrospective observational study was carried out, in which a group of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…This study characterizes adults with moderate-to-severe psoriasis initiating one of the three biologics of interest in routine clinical practice. The median age of patients was 51-52 years, and most patients were 45-64 years of age, similar to published reports [20,25]. The majority of patients were white, as aligned with the 2010 National Health and Nutrition Examination Survey findings, which demonstrated higher prevalence of psoriasis in Caucasians [26].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study characterizes adults with moderate-to-severe psoriasis initiating one of the three biologics of interest in routine clinical practice. The median age of patients was 51-52 years, and most patients were 45-64 years of age, similar to published reports [20,25]. The majority of patients were white, as aligned with the 2010 National Health and Nutrition Examination Survey findings, which demonstrated higher prevalence of psoriasis in Caucasians [26].…”
Section: Discussionsupporting
confidence: 86%
“…In a real-world study conducted in the USA, nearly 60% of patients with moderate-to-severe psoriasis who were on biologic therapy were prescribed concomitant topical corticosteroids [22]; systemic corticosteroids were the most common nonbiologic systemic therapy, with about one-quarter of patients having prior use, followed closely by methotrexate, which is consistent with a recent real-world study [20]. Similar to prior reports, previous exposure to biologic therapies was also high across all treatment cohorts, at around 50% [25,30]. In one study, comparison of realworld treatment patterns among psoriasis patients treated with ixekizumab or adalimumab revealed a higher rate of prior use of biologics in ixekizumab users compared with adalimumab users (65.8% versus 35.8%) [20].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The current findings of favorable treatment patterns among biologic-experienced IXE users compared to SEC users are consistent with findings from clinical trials and other real-world studies examining clinical outcomes [24][25][26]. A real-world study comparing clinical outcomes between IXE and SEC patients with psoriasis who have two or more previous biologic therapies demonstrated a significantly higher PASI 75 (75% improvement in PASI) response among IXE-treated than SEC-treated patients at week 52 (IXE 100% vs. SEC 54.5%; p = 0.039) [25]. Likewise, indirect comparison using network meta-analysis showed that IXE users had higher PASI 90 response rate than SEC (72.1% vs. 67.0%) during 48-52 weeks of treatment [26].…”
Section: Discussionsupporting
confidence: 84%
“…These are specialized helper T-cells producing IL-17 and thereby influencing the NF-kβ pathway, and have been implicated in the pathogenesis of a variety of autoimmune diseases. IL-17 antagonists (e.g., Secukinumab and Ixekizumab) are commercially available and FDA approved for the treatment of ankylosing spondylitis and psoriatic arthritis, and may represent potential agents for LGLL, especially in the setting of association with autoimmune disorders [79][80][81][82][83] (Figure 2).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%